2012
DOI: 10.4269/ajtmh.2012.11-0342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Emergence and Seasonality of West Nile Virus in California

Abstract: Abstract. Temperature has played a critical role in the spatiotemporal dynamics of West Nile virus transmission throughout California from its introduction in 2003 through establishment by 2009. We compared two novel mechanistic measures of transmission risk, the temperature-dependent ratio of virus extrinsic incubation period to the mosquito gonotrophic period (BT), and the fundamental reproductive ratio (R 0 ) based on a mathematical model, to analyze spatiotemporal patterns of receptivity to viral amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 61 publications
2
86
0
1
Order By: Relevance
“…However, it was shown that the replication cycle is completed more quickly in mosquitoes at higher temperatures [38,39], while a clear association was found between extreme heat and outbreak intensity in humans [4,18,22,35,[40][41][42][43]. At the same time, it is important to note that, in some cases, extremely high temperatures begin to slow down mosquito activity.…”
Section: (A) Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, it was shown that the replication cycle is completed more quickly in mosquitoes at higher temperatures [38,39], while a clear association was found between extreme heat and outbreak intensity in humans [4,18,22,35,[40][41][42][43]. At the same time, it is important to note that, in some cases, extremely high temperatures begin to slow down mosquito activity.…”
Section: (A) Temperaturementioning
confidence: 99%
“…In fact, WNV became endemic across most temperate regions of North America [12]. The effects of weather fluctuations on WNV transmission in the USA and Canada have been analysed by several researchers who showed that increased temperatures influence North American WNV distribution and play an important role in the maintenance and amplification of human infection [43,81]. Soverow et al [42] assessed 16 298 human WNF cases from 2001 to 2005 across 17 states in the USA.…”
Section: (B) Climate Change Impact On West Nile Virus Transmissionmentioning
confidence: 99%
“…Crows are a widespread, synanthropic, and highly competent host for WNV . In their mechanistic model developed to track the invasion of WNV into California, Hartley et al (2012) showed that outbreaks are unlikely to occur in the absence of crows or other highly competent amplification hosts. Moreover, in southern California, foci of WNV infection in Culex and humans generally overlapped with areas of high crow density and mortality, suggesting the importance of corvids in amplification of the virus (Reisen et al 2006a).…”
mentioning
confidence: 99%
“…Developing an understanding of short-term lags in the effect of exposure and manifestation of the selected health outcome is crucial for correctly capturing true associations [133,134]. These lags might be driven by complex life cycle processes and/or social determinants such as a lack of timely utilization of health care facilities.…”
Section: (I) Statistical Modelsmentioning
confidence: 99%